Enhancing Table-to-Text Generation with Numerical Reasoning Using Graph2Seq Models - Sulisetyo Puji Widodo; Adila Alfa Krisnadhi (School of Industrial and System Engineering, Telkom University, 2024)
Interpreting data in tables into narratives is necessary because tables cannot explain their own data.Additionally, there is a need to produce more analytic narratives from the results of numericalreasoning on data from tables. The sequence-to-sequence (Seq2Seq) encoder-decoder structure is themost widely used in table-to-text generation (T2XG). However, Seq2Seq requires the linearization oftables, which can omit structural information and create hallucination problems. Alternatively, thegraph-to-sequence (Graph2Seq) encoder-decoder structure utilizes a graph encoder to better captureimportant data information. Several studies have shown that Graph2Seq outperforms Seq2Seq. Thus,this study applies Graph2Seq to T2XG, leveraging the structured nature of tables that can berepresented by graphs. This research initiates the use of Graph2Seq in T2XG with GCN-RNN andGraphSage-RNN, aiming to improve narrative generation from tables through enhanced numericalreasoning. Based on the automatic evaluation of the application of Graph2Seq on the T2XG task, ithas the same performance as the baseline model. Meanwhile, in human evaluation, Graphsage-RNNis better able to reduce the possibility of hallucinations in text compared to the baseline model andGCN-RNN.